Rapid Induction of Multifunctional Antibodies in Rabbits and Macaques by Clade C HIV-1 CAP257 Envelopes Circulating During Epitope-Specific Neutralization Breadth Development - Malherbe, Delphine C.; Wibmer, Constantinos Kurt; Nonyane, Molati; Reed, Jason; Sather, D. Noah; Spencer, David A.; Schuman, Jason T.; Guo, Biwei; Pandey, Shilpi; Robins, Harlan; Park, Byung; Fuller, Deborah H.; et al. (Frontiers in Immunology, 2020)
We report here on HIV-1 immunization results in rabbits and macaques co-immunized with clade C gp160 DNA and gp140 trimeric envelope vaccines, a strategy similar to a recent clinical trial that showed improved speed and magnitude of humoral responses. Clade C envelopes were isolated from CAP257, an individual who developed a unique temporal pattern of neutralization breadth development, comprising three separate “Waves” targeting distinct Env epitopes and different HIV clades. We used phylogeny and neutralization criteria to down-select envelope vaccine candidates, and confirmed antigenicity and conformational integrity of our antigens by interaction with well-characterized broadly neutralizing monoclonal antibodies. Using these envelopes, we performed rabbit studies that screened for immunogenicity of CAP257 Envs from timepoints preceding peak neutralization breadth in each Wave. Selected CAP257 envelopes from Waves 1 and 2, during the first two years of infection that were highly immunogenic in rabbits were then tested in macaques. We found that in rabbits and macaques, co-immunization of DNA and protein envelope-based vaccines induced maximum binding and neutralizing antibody titers with three immunizations. No further benefit was obtained with additional immunizations. The vaccine strategies recapitulated the Wave-specific epitope targeting observed in the CAP257 participant, and elicited Tier 1A, 1B and Tier 2 heterologous neutralization. CAP257 envelope immunogens also induced the development of ADCC and TFH responses in macaques, and these responses positively correlated with heterologous neutralization. Together, the results from two animal models in this study have implications for identifying effective vaccine immunogens. We used a multi-step strategy to (1) select an Env donor with well-characterized neutralization breadth development; (2) study Env phylogeny for potential immunogens circulating near peak breadth timepoints during the first two years of infection; (3) test down-selected Envs for antigenicity; (4) screen down-selected Envs in an effective vaccine regimen in rabbits; and (5) advance the most immunogenic Envs to NHP studies. The results were an induction of high titers of HIV-1 envelope-specific antibodies with increasing avidity and cross-clade neutralizing antibodies with effector functions that may improve the potential for protection in a pre-clinical SHIV model.